The application of a physico-chemical method to the microbiological assay of penicillin and to the study of the dynamics of disinfection - Hollow, Kenneth (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Sc.) -- University of Stellenbosch, 1947.